2010
DOI: 10.1073/pnas.1001733107
|View full text |Cite
|
Sign up to set email alerts
|

A myopathy-linked tropomyosin mutation severely alters thin filament conformational changes during activation

Abstract: Human point mutations in β-and γ-tropomyosin induce contractile deregulation, skeletal muscle weakness, and congenital myopathies. The aim of the present study was to elucidate the hitherto unknown underlying molecular mechanisms. Hence, we recorded and analyzed the X-ray diffraction patterns of human membranepermeabilized muscle cells expressing a particular β-tropomyosin mutation (R133W) associated with a loss in cell force production, in vivo muscle weakness, and distal arthrogryposis. Upon addition of calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 35 publications
0
47
0
Order By: Relevance
“…1 and Table 2). This specific D286G mutation is not directly located in a region where myosin head residues bind (Ochala et al, 2012(Ochala et al, , 2008(Ochala et al, , 2011. Hence, the observed reduction in the intensification of the first MM reflection together with the reduced I 1,1 to I 1,0 ratio (À23% , Table 1) -suggesting a limited proper strong myosin Fig.…”
Section: Disrupted Binding Of Myosin Moleculesmentioning
confidence: 77%
See 1 more Smart Citation
“…1 and Table 2). This specific D286G mutation is not directly located in a region where myosin head residues bind (Ochala et al, 2012(Ochala et al, , 2008(Ochala et al, , 2011. Hence, the observed reduction in the intensification of the first MM reflection together with the reduced I 1,1 to I 1,0 ratio (À23% , Table 1) -suggesting a limited proper strong myosin Fig.…”
Section: Disrupted Binding Of Myosin Moleculesmentioning
confidence: 77%
“…Arrays of approximately 30 fibers were prepared (Iwamoto, 2009;Iwamoto et al, 2001Iwamoto et al, , 2002Iwamoto et al, , 2003Ochala et al, 2012Ochala et al, , 2008Ochala et al, , 2011. For each myofiber, both ends were clamped to half-split gold meshes for electron microscopy (width, 3 mm), which had been glued to precision-machined ceramic chips (width, 3 mm) designed to fit into a specimen chamber.…”
Section: X-ray Diffraction Recordings and Analyzesmentioning
confidence: 99%
“…The physiological mechanism for muscle weakness was further studied in detail in muscle cells by applying X-ray diffraction analysis where the movement of tropomyosin during the activation of muscle contraction can be determined. The results from this study demonstrated that the movement of tropomyosin over actin was impaired by the R133W mutation, which may directly explain the weakness, as this will cause a reduced number of actin-myosin crossbridges [59]. The E41K mutation associated with cap/nemaline myopathy was also studied in vitro on single muscle fibres from patients.…”
Section: Discussionmentioning
confidence: 97%
“…Fibre mechanics and X-ray recordings were performed using established methodologies [9,14,15]. Full details are presented in the supplementary file.…”
Section: Mechanical and X-ray Diffraction Experimentsmentioning
confidence: 99%